Effects of Toxic Compounds in Contaminated Drinking Water for Livestock - Yuningsih . (Indonesian Center for Animal Research and Development, 2005)
Good water quality is a broad term, which encompasses taste, mineral and organic content, salinity, solids, microbes and potential natural or chemical contaminants in the safety level . Due to the rapid development of industrial companies without a proper waste water treatment, the source of drinking water for animal can be contaminated by toxic compounds . Water resources for livestock must be free from the contamination qualitatively as well as quantitatively . This paper describes some contaminants in the drinking water, their effects on livestock, and methods to measure their level. Key words: Water quality, toxic compounds, livestock